The strange dreams of Rover Jones - Armour, Richard Willard; Gurney, Eric. (New York, McGraw-Hill, 1973)
Rover dreams he is the master and that his owner is his four-footed, barking, lovable, troublesome pet.
In verse.
Keywords: Stories in rhyme